A Rare Case of Grade II Chondrosarcoma of the Maxilla: Diagnostic Pitfalls in Histopathology - Rajat, Mohanty; N C, Sangamesh; Abikshyeet, Panda; Jugajyoti, Pathi; Malvika, Raghuvanshi (Bangladesh Journal of Medical Science, 2026)
Background Chondrosarcoma is a rare malignant mesenchymal tumor characterized by persistent cartilaginous differentiation, comprising only 0.1% of head and neck tumors. Within the craniofacial region, commonly affected sites include the larynx, nasal cavity, maxilla, ethmoid and sphenoid bones, and mandible. This report presents a case of Grade II chondrosarcoma of the maxilla presenting a dianostic dilemma in incisional biopsy sample. Case Presentation: A 59-year-old male presented with a one-year history of painless, progressive swelling and discomfort in the right upper jaw. Intraoral examination revealed a well-defined proliferative mass (6 × 4 cm) on the right palate, firm to bony-hard and tender on palpation. Orthopantomogram (OPG) showed an ill-defined radiolucency in the right posterior maxilla extending into the maxillary sinus, with thinning and resorption of the sinus floor and buccal cortex. Histopathological analysis of an incisional biopsy revealed neoplastic chondrocytes within lacunar spaces in a chondroid matrix, with nuclear pleomorphism and hyperchromasia. Although some areas appeared benign, multiple sections confirmed features consistent with Grade II chondrosarcoma. Surgical management included wide local excision via an intraoral infrastructural maxillectomy. Conclusion Craniofacial chondrosarcoma presents significant diagnostic challenges due to its resemblance to benign cartilage tumors. Accurate diagnosis requires a multidisciplinary approach incorporating imaging, biopsy, and thorough histopathological evaluation. Early identification is critical to ensure timely and effective treatment. This case highlights the importance of recognizing rare maxillary malignancies and reinforces the need for vigilance in distinguishing benign from malignant cartilage lesions. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S175-S179